العملات المشفرة تاريخها وحكمها - Saleh, Abdulmajid Obaid Hasan; Ameen Ahmed Abdullah Qasem Anaharib, Ameen (Online Journal of Research in Islamic Studies UM, 2019)
ABSTRACT Virtual money emerged as a form of digital money, and it has the same features of paper money in terms of selling, purchasing and international trade exchange without any material tangible entity or central censorship. The value of this currency has developed over approximately thirty years. The spread of this currency created problems that affect the concept of shar’i (legitimate) exchange such as incursion into gambling, cheat, etc.; and lead to the decline of the central banks’ dominance as well as their monetary and financial policies. Consequently, it negatively affects the real economy in addition to the risks which influence the life of middle class people to the extent that the virtual currencies spread. Hence, it was crucial to understand the reality of virtual money. This paper concludes that the view, which prohibits dealing with this currency, is sounder and better due to the dangers resulted from it. This opinion accords with the shar’i and maqasidic viewpoint.